Soluble interleukin‐2 receptor (sIL‐2r) level is a limited test for the diagnosis of adult secondary hemophagocytic lymphohistiocytosis. (28th May 2020) - Naymagon, Leonard; Tremblay, Douglas; Troy, Kevin; Mascarenhas, John
Abstract: Background: Soluble interleukin‐2 receptor (sIL‐2r) level is used as a diagnostic tool in hemophagocytic lymphohistiocytosis (HLH). However, evidence supporting its use among adults is inadequate. Objective and Methods: We conducted a retrospective study to assess the performance characteristics of sIL‐2r for the diagnosis of adult HLH. Results: One hundred thirty‐two adults with sIL‐2r levels sent for evaluation of HLH over a ten‐year period were included. Sixty‐five (49%) met criteria for HLH. Mean sIL‐2r was significantly higher among patients with HLH relative to all patients without HLH (12942U/ml vs. 6308 U/mL, P = .00311). However, when comparing mean sIL‐2r in the HLH group to those in the non‐HLH group with primary diagnoses of hematologic malignancy (8911 U/mL), sepsis (7127 U/mL), and rheumatologic disease (4624 U/mL), no significant differences were found ( P = .241, P = .178, and P = .0607, respectively). There was only weak correlation between sIL‐2r and diagnosis of HLH ( r = .253). The standard cutoff sIL‐2r > 2400 U/ml yielded a sensitivity of 89.2% and specificity of 38.8%. The area under the curve for the corresponding receiver‐operator curve was 0.691, consistent with a poor discriminating ability for the diagnosis of HLH. Conclusions: sIL‐2r is a limited test for the diagnosis of adult secondary HLH, and its role in this setting should be reevaluated.